Maternal age and pregnancy outcomes in elderly mothers - Amin, Fiza; Tali, Tavseef Ahmad; Ara, Rifat; Amin, Huda (International Journal of Research in Medical Sciences, 2023)
Background: Aim of the study was to compare pregnancy outcomes between women aged 40 or older and those aged 20 to 39 years. Methods: The retrospective cohort study was conducted at SKIMS medical college, Srinagar between March 2017 to April 2019 in which hospital records of 170 patients who delivered during the study period were analysed. Results: Among patients of 40 years old and above, obstetric complications are significantly more frequent, with an increased risk of gestational diabetes, pre-eclampsia, gestational hypertension and caesarean delivery. Fetal risk of IUGR, prematurity was significantly greater in patients 40 years of age or older. Conclusions: A 40-year-old or older mother is more likely to experience medical issues and have more invasive deliveries. Additionally, there is a strong correlation between highly advanced maternal age and unfavourable perinatal outcomes such preterm birth and fetal growth restriction.